2021
DOI: 10.3389/fnut.2021.680391
|View full text |Cite
|
Sign up to set email alerts
|

QTL Mapping for Grain Zinc and Iron Concentrations in Bread Wheat

Abstract: Deficiency of micronutrient elements, such as zinc (Zn) and iron (Fe), is called “hidden hunger,” and bio-fortification is the most effective way to overcome the problem. In this study, a high-density Affymetrix 50K single-nucleotide polymorphism (SNP) array was used to map quantitative trait loci (QTL) for grain Zn (GZn) and grain Fe (GFe) concentrations in 254 recombinant inbred lines (RILs) from a cross Jingdong 8/Bainong AK58 in nine environments. There was a wide range of variation in GZn and GFe concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
5
13
0
Order By: Relevance
“…For example, Gorafi et al (2016) and our group found one wheat Fe QTL near the 496 Mb position on chromosome 5D, and Pu et al (2014) and our team also found one wheat Fe QTL near the 616 Mb position on chromosome 7D. In addition, we found some QTLs in locations similar to those of their counterparts from previous studies, which suggests that at least some of the results of this study are consistent with those of previous studies ( Arora et al, 2019 ; Alomari et al, 2018 ; Crespo-Herrera et al, 2017 ; Cu et al, 2020 ; Rathan et al, 2021 ; Roshanzamir, Kordenaeej & Bostani, 2013 ; Wang et al, 2021a ; Wang et al, 2021b ). No other QTLs reported in the present study were identified in previous studies.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…For example, Gorafi et al (2016) and our group found one wheat Fe QTL near the 496 Mb position on chromosome 5D, and Pu et al (2014) and our team also found one wheat Fe QTL near the 616 Mb position on chromosome 7D. In addition, we found some QTLs in locations similar to those of their counterparts from previous studies, which suggests that at least some of the results of this study are consistent with those of previous studies ( Arora et al, 2019 ; Alomari et al, 2018 ; Crespo-Herrera et al, 2017 ; Cu et al, 2020 ; Rathan et al, 2021 ; Roshanzamir, Kordenaeej & Bostani, 2013 ; Wang et al, 2021a ; Wang et al, 2021b ). No other QTLs reported in the present study were identified in previous studies.…”
Section: Resultssupporting
confidence: 91%
“…The present associated mapping population exhibits a quantitative mode of inheritance for grain Fe concentration, which is in agreement with previous reports ( Tiwari et al, 2009 ; Srinivasa et al, 2014 ). Numerous previous QTL mapping studies have been conducted for wheat grain Fe ( Arora et al, 2019 ; Alomari et al, 2018 ; Cu et al, 2020 ; Gorafi et al, 2016 ; Rathan et al, 2021 ; Velu et al, 2017 ; Wang et al, 2021a ; Wang et al, 2021b ). A previous study conducted by Pu et al (2014) reported five QTLs for grain Fe on chromosomes 2B, 4A, 5A, 5B, and 7D using recombinant inbred line population of wheat, and these QTLs coincided with the lociAX-111087936, AX-109551612, AX-110549899, AX-109486399, and AX-95112608 identified in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a separate study, eight major QTLs for GZn and four for GFe were detected on chromosomes 1B, 1D, 2B, 3A, 3D, 6B, 7A, and 7B using a total of 127 hexaploid RILs, which accounted for 10.0-31.0% of the phenotypic variation. Wang et al (2021) detected one major QTL for GZn and one for GFe on chromosome 4D, which was a pleiotropic QTL. Liu et al (2019) detected 1 major QTL for GZn and 2 for GFe on chromosomes 2B, 3B, and 5A, which accounted for 10.8-14.6% of the phenotypic variation.…”
Section: Introductionmentioning
confidence: 92%
“…SNPs closely linked to the target QTLs were transformed into KASP markers. PolyMarker (http://www.polymarker.info/) was used to design KASP primers (Wang et al 2021). A uorescent quantitative real-time (qRT)-PCR instrument (C1000 Touch; Bio-Rad, California, USA) was used for gel-free uorescent signal scanning and allele separation (Chandra et al 2017).…”
Section: Conversion Of Snps To Kompetitive Allele Speci C Pcr (Kasp) ...mentioning
confidence: 99%